False things and things unable to be true: representation and fraud in Chaucer - O'Connell, Brendan (Trinity College (Dublin, Ireland). School of English, 2008)
This thesis was born of two assumptions about Chaucer's Canterbury Tales. The first was that the rejection of poetry in the Parson's Prologue and Tale and the Retractions was in no sense ironic, but rather the expression, in however conventional a form, of a genuine concern with the ethical implications of fiction. The other was a conviction that the alchemical tales of the Second Nun and the Canon's Yeoman were of crucial significance in understanding this conclusion. During the course of my research into literary accounts of alchemy, I discovered a remarkable overlap between the depiction of the falsifiers in Dante's infernal circle of Fraud and the discussion of the relationship between Nature and Art in Jean de Meun's part of the Roman de la Rose. These parallels suggested a way of relating acts of falsification (such as counterfeiting, alchemy and impersonation) to artistic representation, offering a useful lens through which to examine medieval attitudes to the ethical implications of taletelling. This thesis teases out the implications of this analogy, and demonstrates that it was a pervasive influence on the works of Chaucer.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin